OPTIMIZING THE ROLE OF EDUCATORS IN DEVELOPING THE PROGRESS OF DIGITAL TECHNOLOGY-BASED EDUCATIONAL INSTITUTIONS - Asrijal, Andi; Indrawati, Raden Ajeng (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract Integrating technology in education is crucial in the digital era to create a dynamic and effective learning environment. However, successfully implementing digital tools depends on educators' roles and abilities. This community service empowers educators to integrate digital technology into their teaching practices effectively. This service method uses Participatory Action Research (PAR), which includes a series of collaborative workshops and the formation of a Professional Learning Community (PLC). These workshops provide hands-on training on digital tools, while PLCs offer a platform for ongoing peer support, knowledge sharing, and collaborative problem-solving. The service results show a significant increase in educators' self-confidence and proficiency in digital technology. Additionally, PLCs play a critical role in sustaining this progress by fostering a culture of continuous learning and innovation. The project also observed positive impacts on student engagement and learning outcomes, demonstrating the benefits of effective digital integration in education. In conclusion, this project highlights the importance of targeted professional development and ongoing support for educators in the digital transformation of educational institutions. Addressing resource gaps and ensuring active engagement from school leaders is critical to sustaining this progress. Ultimately, optimizing the role of educators is the key to creating an inclusive and engaging learning environment in the digital era.